Síntesis y caracterización de Nanopartículas de Sílice como Potencial Vehículo de Compuestos Bioactivos - Loyola Cisneros, Kelly Rocío (2023)
One of the main problems in the health area is the low efficiency of the currently used drug delivery systems. As a result, in recent years there has been an increased interest in the development of new delivery vehicles, highlighting the use of silica-based materials since they are reported to be biocompatible, non-toxic, mechanically and chemically stable, as well as having a functionalizable chemical surface. In this work we present the synthesis of spherical silica nanoparticles (NPsSiO2) synthesized by the modified Stöber method, with the use of an alkoxide precursor tetraethyl orthosilicate, in aqueous medium and ammonium hydroxide as catalyst. It was characterized to determine the presence of siloxane (Si-OSi), silanol (Si-OH) and amino groups was determined by Fourier transform IR spectroscopy (FT-IR), by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) the spherical morphology was checked while the particle size in solution was determined by dynamic light scattering (DLS) in aqueous medium (150 nm).